Copper‐Catalyzed Cyanomethylation of Substituted Tetrahydroisoquinolines with Acetonitrile. Issue 15 (12th July 2016) - Zhang, Wei; Yang, Shiping; Shen, Zengming
Abstract: A novel method for the synthesis of cyanomethylated tetrahydroisoquinolines has been developed with mild reaction conditions, good yields and a broad substrate scope. Acetonitrile, a common solvent, is for the first time used as a pronucleophile for this type of two sp 3 C−H bonds cross‐dehydrogenative coupling (CDC) reaction. A new oxidative system (CuCl2 /TEMPO/Cs2 CO3 ) has been established by our group, in which the mild TEMPO reagent was found to be a highly efficient oxidant. Abstract :